Influence of Uncoupled Diblock Molecules on Mechanical Properties of Styerene/Butadiene/ Styrene Triblock Copolymers - Adhikari, Rameshwar (Nepal Journal of Science and Technology, 2012)
The influence of the presence of uncoupled polystyrene-block-polybutadiene (SB) diblock chains to polystyrene-block-polybutadiene-block-polystyrene (SBS) triblock copolymers on the mechanical properties of the latter has been studied by means of tensile testing and dynamic mechanical analysis preparing several lamellae forming SBS/ SB blends through solution casting. The microphase-separated morphology of the samples was investigated by transmission electron microscopy. Both large strain deformation tensile deformation behaviour and viscoelastic properties of the SBS block copolymers were found to be affected appreciably by the presence of uncoupled SB diblock. The storage modulus of linear SBS was found to drop more sharply in the plateau region than for the radial SBS at the same SB content. At low SB content (up to 20 wt.-% for linear SBS and still higher for radial one), the overall tensile properties was not negatively influenced. On the whole, star block copolymers were found to be less sensitive towards the presence of diblock. DOI: http://dx.doi.org/10.3126/njst.v12i0.6493 Nepal Journal of Science and Technology 12 (2011) 149-156